Hyper-resolution naturalized streamflow data for Geum River in South Korea (1951–2020) - Byeong-Hee Kim; Young-Oh Kim; Jonghun Kam (Scientific Data)
Abstract Long-term streamflow data at a hyper-resolution (less than 1 km) is essential for hydroclimatic extreme and ecological assessment, which is not available over a river basin where rapid socioeconomic growth have been experienced. Here, we use the Variable Infiltration Capacity-River Routing Model (VIC-RRM) to reconstruct naturalized daily streamflow at 90–meter resolution for the Geum River, one of South Korea’s major rivers, over 1951–2020. VIC-RRM demonstrates high temporal consistency with a correlation coefficient exceeding 0.6 for observed streamflow seasonality at over 60% of the 90 gauge stations along the Geum River. However, 36% of the stations show low modified Kling-Gupta Efficiency (0.2–0.4), primarily due to uncertainties in runoff data and human disturbance impacts like irrigation and reservoir storage. Our simulated naturalized data reveal decadal variability in the 1990s and an increase in day-to-day variability of the Geum River in the 2010s compared to those in the 1970s. This dataset provides physically consistent naturalized streamflow data for reference data to evaluate climate change-driven changes in streamflow for the Geum River.